2022
DOI: 10.18552/ijpblhsc.v10i1.733
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based Learning Experiences in Stuttering Management Delivered Online: What Do Students, Clinical Educators and Simulated Patients Think?

Abstract: Speech pathology students are required to demonstrate competency across a range of practice areas. There are, however, limited opportunities for students to access clinical placements in the area of stuttering. Simulation-based learning (SBL) activities have proven to be effective in increasing students’ clinical experience in this area. Due to the COVID-19 pandemic, the delivery of in-person SBL programs was not feasible, resulting in a shift to online provision. The aim of this study was to investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous research in telesimulation has predominantly explored training and development for medical and nursing staff [ 6 8 , 30 , 31 ]. Although many learnings can be taken from this previous work, to our knowledge, this is the first study to explore the use of telesimulation in pediatric feeding management in speech pathology, apart from in a clinical education setting with university students [ 9 , 10 ]. Overall, it was concluded that telesimulation was a feasible teaching modality for infant feeding management, and participant feedback was generally positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in telesimulation has predominantly explored training and development for medical and nursing staff [ 6 8 , 30 , 31 ]. Although many learnings can be taken from this previous work, to our knowledge, this is the first study to explore the use of telesimulation in pediatric feeding management in speech pathology, apart from in a clinical education setting with university students [ 9 , 10 ]. Overall, it was concluded that telesimulation was a feasible teaching modality for infant feeding management, and participant feedback was generally positive.…”
Section: Discussionmentioning
confidence: 99%
“…Telesimulation is defined as "a process by which telecommunication and simulation resources are utilized to provide education, training, and/or assessment to learners at an off-site location" [5, p133]. Telesimulation as a teaching modality has been explored in medical and nursing education [6][7][8] and in clinical education settings for allied health students [9,10]. Results have demonstrated that, in a similar way to in-person simulation [11], speech pathology students accessing telesimulation reported increased confidence and perceived positive impact on clinical skills [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, SPs argued that online interactions were less effective for full physical examinations. [75][76][77][78][79]…”
Section: Discussionmentioning
confidence: 99%
“…Further studies on how SPs can improve their capacity to evaluate different personality styles and students' learning preferences may be helpful for portraying history taking and physical examinations. However, SPs argued that online interactions were less effective for full physical examinations 75–79 …”
Section: Discussionmentioning
confidence: 99%
“…In common with the first part of the COVID-19 special issue, many of the papers consider, reflect on or evaluate educational innovations designed and implemented at speed. In most cases, these involved digital adaptations of previously existing learning experiences, supervision arrangements, and assessments (McCarthy, 2022;Skeat et al, 2022;Dicken et al, 2022;Penman et al, 2022). In others, new activities and events were introduced; Dicken et al ( 2022) replicated the changes to real practice by introducing simulation-based learning and video interactions in a social work setting in the United Kingdom, and Cushen-Brewster et al ( 2022) introduced paid placements for nursing students in the UK in collaboration with national groups and regulatory bodies.…”
Section: Editorial: Resilience and Transformation In And Beyond The C...mentioning
confidence: 99%